Reversible pulmonary fibrosis after receiving anti-thymocyte globulin and cytomegalovirus infection - A. Kiani; B. Bromand; R. Sami (The Journal of Qazvin University of Medical Sciences, 2015)
In the past decade, pulmonary dysfunction has been reported due to treatment with anti-thymocyte globulin (ATG) in patients suffering from rejection of organ transplantation or aplastic anemia. Cytomegalovirus (CMV) infection is one of the common infections in recipients of organ transplantation. In this report, a 46 years old man underwent treatment with ATG due to rejection of kidney transplantation and developed pulmonary infiltration. Cytomegalovirus antigen load was raised in the serum. After discontinuation of ATG and treatment with ganciclovir, fibrosis and reduction of lung volume was developed. The resultant fibrosis was completely resolved after one month and the general condition of the patient was improved. In conclusion, fibrotic pattern in pulmonary HRCT cannot prove the irreversibility of the lesion.